2022
DOI: 10.1111/padm.12827
|View full text |Cite
|
Sign up to set email alerts
|

What's in a name? The politics of name changes inside bureaucracy

Abstract: In this article, we examine the effects of political change on name changes of units within central government ministries. We expect that changes regarding the policy position of a government will cause changes in the names of ministerial units. To this end we formulate hypotheses combining the politics of structural choice and theories of portfolio allocation to examine the effects of political changes at the cabinet level on the names of intra‐ministerial units. We constructed a dataset containing more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…This transitional understanding of structural change allows a more flexible empirical assessment, without an a priori judgment on whether a distinct structural change event constitutes a creation, maintenance, or termination. Accordingly, different research interests can be accomplished, such as studying all or highlighting only particular structural transitions in government (Fleischer et al, 2023; Yesilkagit et al, 2022) or analyzing the risk for organizations facing different structural transitions (Yesilkagit, 2020). Put differently, these further assessments of the official documentation on government structures over time allow to establish structural change explicitly and enable more nuanced empirical analyses that consider complete legislative periods during which political control vis‐à‐vis the permanent bureaucracy may be exercised in structural transitions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This transitional understanding of structural change allows a more flexible empirical assessment, without an a priori judgment on whether a distinct structural change event constitutes a creation, maintenance, or termination. Accordingly, different research interests can be accomplished, such as studying all or highlighting only particular structural transitions in government (Fleischer et al, 2023; Yesilkagit et al, 2022) or analyzing the risk for organizations facing different structural transitions (Yesilkagit, 2020). Put differently, these further assessments of the official documentation on government structures over time allow to establish structural change explicitly and enable more nuanced empirical analyses that consider complete legislative periods during which political control vis‐à‐vis the permanent bureaucracy may be exercised in structural transitions.…”
Section: Methodsmentioning
confidence: 99%
“…They also highlighted the relevance of political determinants (Götz et al, 2018; Pollitt, 1984; Ryu et al, 2020; Sieberer et al, 2019). More recently, scholars turned toward the change of formal structures inside ministerial departments and demonstrated that such political determinants also matter for these levels of government organizations (Fleischer et al, 2023; Kuipers et al, 2021; Yesilkagit et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Sieberer et al (2021) reveal the importance of the arrival of new parties or prime ministers to explain ministerial portfolios changes after general elections, and Fleischer et al (2022) demonstrate the relevance of the cabinet's ideological viewpoints to structural changes in the inner branches of ministerial departments. Because they are the consequence of the political will to adjust their policies as well as to signal policy changes to their constituencies (Moe & Caldwell, 1994), changes in portfolio and bureaucracy reflect substantive policy options (Yesilkagit et al, 2022). These changes can also be made as an adaptation to the political context while the executive is in office, such as reshuffles, policy scandals or major reforms (Bertelli & Sinclair, 2015).…”
Section: Literature On Pledge Fulfilment and Ministerial Instabilitymentioning
confidence: 99%
“…We assume that these variations matter in the UN system as well: IPAs servicing actors as their principals who engage in policy- and program-related tasks – in the UN system these are mainly regional commissions as well as funds and programs – allow to address policy agendas in the inner structures rather directly, for example, by signalling priorities, shifting resources and gaining internal and external actors’ attention (Goetz & Patz, 2017; cf. Yesilkagit et al, 2021). However, these policy- and program-related principals are often bound to long-term policy preferences set by the UN member states that can neither be adjusted nor abolished easily.…”
Section: Structural Change In International Public Administrationsmentioning
confidence: 99%